The Effectiveness of the European Approach to Irregular Migration – A Legal-economic Assessment (Polish Yearbook of International Law, 2025)
There are few certainties in the field of migration. From the factors that drive migrants to flee their countries and the conditions they expect to find in the destination country to migrants’ flows, routes and methods, migration policy is constantly functioning within a field of uncertainty. Yet, the importance of better managing migration processes is becoming increasingly relevant due to the multiple factors that stimulate the international movement of people, such as conflict, political or economic instability or climate change. The uncertainty surrounding the European Union’s (EU) ability to manage migration has spurred a twofold approach: the criminalisation of migrant smuggling (in an all-encompassing way) and the externalisation of migration policy through agreements with third countries. However, are these approaches effective, or should the EU consider alternative strategies to address the challenges posed by irregular migration? The purpose of this article is to evaluate the effectiveness of the EU’s policies on irregular migration, by exploring firstly the effectiveness of criminal law in deterring migrant smuggling and secondly the EU’s recent emphasis on externalisation. The consequences of both are examined in an effort to determine their effectiveness towards the objective. The article concludes with some suggestions for the way forward.